2020
DOI: 10.32677/ejms.2020.v05.i02.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diarrhea and its associated risk factors in children aged 1–60 months at Aba, South East Nigeria

Abstract: Background: Diarrhea is a major cause of childhood morbidity and mortality worldwide, particularly in low resource nations. To achieve the Sustainable Developmental Goal 3.2, effective steps should be taken to stem the tide of childhood diarrhea and its associated mortality. Objective: The objective of the study was to determine the prevalence of diarrhea and its associated risk factors in children aged 1-60 months presenting to our health facility. Materials and Methods: In the present retrospective study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Specific disease analysis showed sepsis/septicemia; congenital infectious and parasitic diseases; and slow fetal growth, malnutrition and short gestation; and diarrhea were the leading causes of under-five mortalities in this study. Onyeanugha et al 21 and Ibeneme et al 22 had both reported sepsis, malaria and diarrhea as the chief causes of under-five mortalities in Aba and Umuahia, Nigeria, respectively. On the other hand, Odejimi et al 23 and Adewemimo et al 24 reported malaria, diarrhea and pneumonia as the leading causes of mortality in north/southern Nigeria and 36 states of Nigeria, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Specific disease analysis showed sepsis/septicemia; congenital infectious and parasitic diseases; and slow fetal growth, malnutrition and short gestation; and diarrhea were the leading causes of under-five mortalities in this study. Onyeanugha et al 21 and Ibeneme et al 22 had both reported sepsis, malaria and diarrhea as the chief causes of under-five mortalities in Aba and Umuahia, Nigeria, respectively. On the other hand, Odejimi et al 23 and Adewemimo et al 24 reported malaria, diarrhea and pneumonia as the leading causes of mortality in north/southern Nigeria and 36 states of Nigeria, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-three percent of the burden of diarrheal and enteric diseases is associated with poor access to adequate water, sanitation and hygiene (WASH) and is disproportionately borne by the poorest children ( UNIEF, 2020). Onyearugha, et al, (2020) reported a prevalence of 11.2 % and mortality of 22% in Abia state. This high mortality rate due to diarrhea could undermine the achievement of the Sustainable Development Goals (SDGs) of reducing child mortality to 25 deaths per 1000 live births or less by 2030 if not controlled (United Nation, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research across different parts of Nigeria have shown that each child under the age of five could have as many as 4-7 episodes of diarrhea yearly (Dairo, et al, 2017;Grenov et al, 2019). In Abia state, there is erratic supply of portable water, poor sanitation facilities in most of the houses, and has the highest prevalence of diarrhea diseases among all the communities in southeast, from the health facility records ( Onyearugha et al, 2020). In addition Ukegbu, & Ukegbu, (2010) reported that mothers of under five in Abia state had poor perception of diarrhea and they lacked accurate knowledge about the specific causes of childhood diarrhea, as they associated it with divergent causes.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of diarrhoea can be successfully treated at home with Oral Rehydration Therapy (ORT), with only a few cases requiring treatment in an emergency ward with intravenous fluid and antibiotics. 8 A two-year retrospective study conducted by Onyearugha et al 9 in an Eastern Nigerian tertiary hospital among under-five children admitted to the emergency ward for diarrhoea found an 11.2% prevalence of diarrhoea and a 22% case mortality rate. A four-year retrospective study of 394 children admitted to the emergency ward of a tertiary hospital in Port-Harcourt, Nigeria, found a 3.6% case mortality rate but no information on the prevalence of diarrhoea.…”
Section: Introductionmentioning
confidence: 99%